2015
DOI: 10.1016/j.jrras.2014.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Radiological safety assessment and determination of heavy metals in soil samples from some waste dumpsites in Lagos and Ogun state, south-western, Nigeria

Abstract: RadioactivityHeavy metals a b s t r a c t Assessment of naturally occurring radionuclides and heavy metals in 5 major dumpsites around Lagos and Ogun State, Nigeria, was carried-out to determine the natural radionuclide and heavy metals in the dumpsites and to evaluate the hazards these may have on the public. Radionuclide concentrations were determined using gamma-ray spectrometry with NaI (Tl) detector. The mean activity concentrations of 226 Ra, 232 Th and 40 K in the soil samples were 23.840.9 ± 42.0 in Og… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 8 publications
2
14
0
Order By: Relevance
“…2). Similar observation has been reported by (Ademola et al, 2015). Higher activity concentrations of the radionuclides were obtained in the top soil samples from Idowale dumpsites (Fig.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…2). Similar observation has been reported by (Ademola et al, 2015). Higher activity concentrations of the radionuclides were obtained in the top soil samples from Idowale dumpsites (Fig.…”
Section: Resultssupporting
confidence: 90%
“…Human activities create wastes and the way these are handled, stored, collected and disposed can give rise to impacts on the environment and public health (Ademola et al, 2015). Hazardous waste can cause pollution, damage to health and even death.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Soil is one of the major recipients of these waste products and the main reservoir of these naturally occurring radionuclides. They are transferred to humans through a number of pathways such as ingestion, dermal contact and inhalation of radon gas [9]. Radionuclides may pose a long-term risk even in very low concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…The site specific safety analysis identified important tasks for research and development which would have not been possible by a generic safety analysis. Ademola et al, (2015) carried out assessment of naturally occurring radionuclides and heavy metals in 5 major dumpsites around Lagos and Ogun State, Nigeria and to evaluate the hazards these may have on the public. The results of this study showed 226 Ra and 232 Th were lower than the world average but higher for 40 K and the analysis of heavy metal concentrations indicated that there is presence of Cadmium, Zinc and Copper in high proportion.…”
mentioning
confidence: 99%